Squamous cell carcinoma as a primary pleural tumor – case report - Szklener, Katarzyna; Kopystecka, Agnieszka; Hatala, Patrycja; Gruba, Martyna; Glaza, Mateusz; Mańdziuk, Sławomir (Journal of Education, Health and Sport, 2022)
The differential diagnosis of primary pleural tumors is a very difficult challenge. The clinical symptoms are insufficient to make a clear and definitive diagnosis. This report presents the case of a 63-year-old male patient who was admitted to Department of Pulmonology due to evidence of increasing respiratory failure due to COVID-19 infection. The X-ray showed massive infiltrate on the left pleural cavity. A bronchofiberoscopy was performed with material removal for histopathological examination. No tumor cells were found in the first pathomorphology report. A videothoracoscopy was performed, in which excerpts from the wall and pleura of the lungs were taken. Pathomorphologic findings excluded mesotheliomas and adenocarcinomas, and after additional reactions a low-differentiated squamous cell carcinoma with adenomatoid differentiation features. The final diagnosis was squamous cell carcinoma. This case highlights that the diagnosis of tumors of the pleura requires cooperation between pathomorphologists and clinicians. Further studies are needed to associate COVID-19 infection with the occurrence of rare pleural tumours.